Official Financing : Recent Developments and Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This study provides information on official financing and the debt situation of developing countries. It discusses issues related to trade finance in financial crises, and the challenge of maintaining external debt sustainability in debtor countries. It updates the 2001 edition of Official Financing for Developing Countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet